Polekowe zapalenie skóry wywołane imatynibem u pacjentki z nowotworem podścieliska przewodu pokarmowego - opis przypadku - Hanna Myśliwiec; Anna Baran; Iwona Flisiak; Bożena Chodynicka (Termedia Publishing House, 2011)
Introduction. Gastrointestinal stromal tumour (GIST) is a rare mesenchymaltumour of the gastrointestinal tract and mesentery. Standardtreatment is surgical resection. First-line therapy of unresectable ormetastatic GIST is imatinib mesylate - a tyrosine kinase inhibitor.Objective. The aim of this paper is to present a patient with GIST inwhom treatment with imatinib caused dermatitis as an adverse effectand a change of therapy was necessary.Case report. We present a case of a 57-year-old woman with nonoperativeGIST diagnosed 2 years ago in whom, after 3 months of treatment with imatinib, papulo-erythematous, pruritic eruption on the trunk,lower and upper extremities and face occurred. The histopathologicalpicture corresponded with lichenoid reaction caused by the drug.Despite lowering the dose of imatinib, new infiltrated lesions with atendency to disintegration were observed. Due to systemic (intravenouspulses of corticosteroids, antihistaminics) and topical treatment(corticosteroid ointments) and the change of imatinib for a second-linedrug, sunitinib, improvement of skin lesions was observed.Conclusions. Therapy with imatinib is generally well tolerated, butdermatitis can appear in 30% of patients taking this drug. In the presentedcase with unresectable GIST therapy with imatinib caused skincomplications.